Delayed complications after severe clozapine intoxication: a case report. The pharmacokinetic profile of clozapine and it's important role in the course of symptoms. (September 2019) - van Helvoort, Marloes; van Eijndhoven, Philip; Schellekens, Arnt; Pop-Purceleanu, Monica; Kramers, Cornelis; Batalla, Albert
Abstract : Clozapine intoxications have a varied clinical presentation and may have severe complications. Management and treatment guidelines rarely highlight the risks of delayed clinical presentations. We present the case of a 50-year-old man showing severe complications 15 hours after intoxication with 4200 mg clozapine. Treatment consisted of strict monitoring, including vital support and regular clozapine blood levels. Clinical presentations may be delayed up to 5 days after intoxication, for which strict monitoring of clinical symptoms and vital functions during this period is of major importance. We discuss the clinical course of clozapine intoxication, the value of sampling clozapine blood levels and provide an overview of the current treatment guidelines, which we suggest to update to include the management of delayed complications.